A Self-Controlled Prospective Study between Methylprednisolone and Dexamethasone Inter-Laminar Epidural Steroid Injection in Radicular Pain for Prolapse Intervertebral Disc in Lumber Vertebrae - Ashutosh Parate1 , Nitin Shamal2 , Vasant Gawande3 , Kunal Saoji4 , Ankit Mittal5 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Previous studies have shown varying results with trans-foraminal approach epidural steroidinjections performed with particulate versus non-particulate corticosteroids. The purpose of this study was toinvestigate the difference in pain relief and functional improvement between particulate and non-particulatelumbosacral (MIL) in patients who had undergone both injections through intra-laminar approach. Method:This was a self-controlled, prospective study of 40 patients who underwent both a methylprednisolone anda dexamethasone intra-laminar injection to the same vertebral level and side. Primary outcomes includedpain relief according to the visual analogue scale (VAS) and functional improvement determined by a yes/noanswer to questions regarding mobility and the activities of daily living. Post-injection data was recorded at6, 12, and 24 weeks. Results: A decrease in VAS scores of-3.6 +/- 3,- 3.2 +/- 3.2,-3 +/- 3.1 is noted in methylprednisolone group as compared to better VAS score projected in patients with dexamethasone group assuggested-3.9+/- 3.2,-3.1 +/- 2.9,- 2.2 +/- 3.2 at 6 weeks, 12 weeks and 24 weeks respectively. Conclusions:Findings positively supports the use of non-particulate steroids for lumbar prolapse inter-vertebral disc withradicular pain in contrast of safety use of particulate steroids for one of treatment modality in dealing withlocalized or radicular pain